2000
DOI: 10.1081/clt-100100926
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Toxicity, Clinical Features, and Management of Diquat Poisoning: A Review

Abstract: After rapid confirmation of the diagnosis using a qualitative urine test, gut decontamination may be considered in patients who present within 1 hour of a life-threatening ingestion (>6 g). Supportive measures including fluid and electrolyte replacement should then be employed. Although hemofiltration and hemodialysis are of proven value if renal failure supervenes, there is no clinical evidence that hemodialysis or hemoperfusion removes toxicologically significant amounts of diquat, thereby reducing the risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
164
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(172 citation statements)
references
References 28 publications
5
164
1
2
Order By: Relevance
“…However, PQ (but not MPTP or rotenone) is a potent redox cycler, readily converting to a free radical that interacts with molecular O 2 to generate superoxide anions and other ROS within mitochondria (51,120) (Fig. 8).…”
Section: Paraquat Metabolism and Mitochondrial Mechanisms Of Neurotoxmentioning
confidence: 99%
“…However, PQ (but not MPTP or rotenone) is a potent redox cycler, readily converting to a free radical that interacts with molecular O 2 to generate superoxide anions and other ROS within mitochondria (51,120) (Fig. 8).…”
Section: Paraquat Metabolism and Mitochondrial Mechanisms Of Neurotoxmentioning
confidence: 99%
“…5 The clinical manifestations range from local irritation to multiple-organ failure and death. Systemic manifestations depend on the amount ingested, and patients can be classified into 3 categories (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…However, the mortality rate of PQ poisoning has been reported to range from 50 to 90% when the pesticide is ingested either accidentally or intentionally as a suicide attempt (1). A previous study suggested that absorbed PQ requires removal from the bloodstream in order to improve the survival rate of patients with severe PQ poisoning (2).…”
Section: Introductionmentioning
confidence: 99%